2021
DOI: 10.1016/j.isci.2021.102972
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptome analysis of diffuse large B cells in cerebrospinal fluid of central nervous system lymphoma

Abstract: Summary Diffuse large B cells in the cerebrospinal fluid (CSF-DLBCs) have offered great promise for the diagnostics and therapeutics of central nervous system lymphoma (CNSL) leptomeningeal involvement. To explore the phenotypic states of CSF-DLBCs, we analyzed the transcriptomes of more than one thousand CSF-DLBCs from six patients with CNSL diffuse large B-cell lymphoma (DLBCL) using Smart-seq2 single-cell RNA sequencing. CSF-DLBCs were defined based on abundant expression of B-cell markers, the a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…BC CSF‐CTCs had great heterogeneity shown on the cell‐cycle state and CTAs expression (Figure 5B,C), same as LC CSF‐CTCs 3 and CSF‐DLBCs 4 . CSF‐CTCs in basal‐like subtype, which always has higher probability of metastases and worse prognosis than other subtypes, showed highest proliferation ability (Figure 5A,B).…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…BC CSF‐CTCs had great heterogeneity shown on the cell‐cycle state and CTAs expression (Figure 5B,C), same as LC CSF‐CTCs 3 and CSF‐DLBCs 4 . CSF‐CTCs in basal‐like subtype, which always has higher probability of metastases and worse prognosis than other subtypes, showed highest proliferation ability (Figure 5A,B).…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have shown the CTAs characteristics of CSF malignant cells of LC 3 and central nervous system lymphoma. 4 Here, we focused on CTAs expression ( http://www.cta.lncc.br/modelo.php ) in the five subtype‐specific CSF‐CTCs. BC CSF‐CTCs had higher expression of 11 CTAs (Figure 5C , Table S6 ; PCT in CSF‐CTCs > 0.05), compared to normal breast epithelial cells of basal clusters and luminal clusters from three samples (GSE113196, Normal sample 4–6, N4–N6).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations